Aspectos de la historia del Imperio Romano: Textos traducidos de Morstein-Marx, Rosenstein, Mattingly, Ziolkowski, Grey y Drinkwater - Santos, Diego (Ed.) (Memorabilia, 2017)
This book brings together works on different aspects of the Roman Empire history from its inception to its terminal crisis in the West.